Wiring Techniques for the Fixation of Trochanteric Fragments during Bipolar Hemiarthroplasty for Femoral Intertrochanteric Fracture: Clinical Study and Technical Note - Lee, Joong-Myung (Hip Pelvis, 2017)
PURPOSE: Femoral intertrochanteric fractures are common in the elderly. Appropriate surgical fixation of trochanteric fracture fragments can restore normal anatomical structure and ambulation, and can aid in the recovery of biomechanical function of the hip. We evaluated clinical outcomes of bipolar hemiarthroplasty using a wiring technique for trochanteric fracture fragment fixation. MATERIALS AND METHODS: From September 2006 to February 2015, a total of 260 cases underwent simultaneous bipolar hemiarthroplasty and wire fixation. A total of 65 patients (69 hips) with an average age of 78 years and more than one year of follow-up was included in the study. Using pre-, postoperative and follow-up radiograms, we evaluated wire fixation failure and also assessed changes in walking ability. RESULTS: Loosening or osteolysis around the stem was not observed; however, we did observe bone growth around the stem (54 cases), cortical hypertrophy (6 cases), a wide range of sclerotic lines but no stem subsidence (1 case), wire breakage (9 cases), and fracture fragment migration with no significant functional deficiency (2 cases). CONCLUSION: Our study showed that additional wiring for trochanteric fracture fragment fixation following bipolar hemiarthroplasty can help restore normal anatomy. The added stability results in faster rehabilitation, and good clinical and radiographic outcomes. We recommend this procedure in this type of fracture.